Efecto de los procesos de soldadura al arco en las propiedades mecánicas y microestructura en aceros de alta resistencia y baja aleación (2020)
The arc welding processes generate microstructural changes in the welded metals due to the contributions of heat, this leads to changes in the mechanical properties. In this monograph we sought to study the effect generated by these processes on the mechanical properties and microstructure of the joints, and to correlate this effect as an indicator of the weldability of these materials. Different investigations were analyzed in which the influence of various arc welding processes was observed, changing multiple parameters of the processes, as well as the heat inputs generated during welding on different high strength and low alloy steels (HSLA). According to the analysis carried out, it was found that there is a correlation between the type of microstructure and the mechanical properties and these depend directly on the heat input to which the material is subjected during the welding process. It was also possible to determine that the little variation in mechanical properties and microstructure are a clear indicator of the good weldability of these steels.